The Gut-Blood Axis: A Literature Review on the Role of Gut Microbes and Probiotics in the Management of Anaemia (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Anaemia, a condition characterized by a deficiency in red blood cells or haemoglobin, remains a global public health challenge affecting nearly a third of the world's population. Traditional management strategies primarily focus on nutrient supplementation (e.g., iron, vitamin B12, folate) and treating underlying causes. However, variable efficacy and side effects of these approaches have prompted the exploration of novel adjuvants. The human gut microbiome, a complex ecosystem of trillions of microorganisms, is increasingly recognized as a critical regulator of host physiology, including nutrient absorption and immune function. This literature review synthesizes current evidence on the mechanisms by which gut microbes and their therapeutic derivatives, probiotics, influence the pathogenesis and management of anaemia. We explore the triad relationship between the gut microbiota, iron homeostasis, and inflammation, detailing how specific bacterial taxa can enhance or inhibit iron absorption. Furthermore, we examine the direct role of microbes in the synthesis of folate and vitamin B12, essential cofactors for erythropoiesis. Evidence from preclinical and clinical studies demonstrating the efficacy of various probiotic strains, particularly Lactobacillus and Bifidobacterium, in improving haemoglobin status is critically appraised. The review also discusses the potential of synbiotics and postbiotics as next-generation therapeutic tools. Finally, we identify key research gaps and future directions, concluding that targeted modulation of the gut microbiome represents a promising, multifaceted strategy for the prevention and management of various forms of anaemia, moving beyond conventional nutrient-replacement paradigms.